Fatal Aortoesophageal Fistula Complicating Placement of a 20-mm Lumen-Apposing Metal Stent for Refractory Esophagojejunal Anastomotic Stricture. Issue 3 (19th March 2021) - Patel, Rupal H.; Everett, Brendan T.; Akselrod, Dmitriy; Frasca, Joseph D.; Gordon, Stuart R.
ABSTRACT: We report the case of a patient with a benign refractory esophagojejunal anastomotic stricture for which a 20-mm lumen-apposing metal stent was placed, resulting in a fatal aortoenteric fistula. We report this case to alert others to this potential complication of LAMS placement for esophageal strictures and recommend caution when using the 20-mm LAMS in similar settings.